Research note: A feasible way to implement a citizen's income - Malcolm Torry (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Citizen's Income - an unconditional and nonwithdrawable income for every individual - would offer many advantages, but transition from the UK's current largely means-tested benefits system to one based on a Citizen's Income might generate initial losses for some low-income households, and this could make a Citizen's Income politically unattractive. This paper employs EUROMOD to study the initial losses that a variety of different Citizen's Income schemes would generate, and finds that in those schemes in which a Citizen's Income replaces most means-tested benefits, substantial household losses would occur, both generally and for households in the lowest disposable income decile, whereas where means-tested benefits are not abolished, but instead the Citizen's Income reduces means-tested benefits in the same way that other existing income does, almost no households in the lowest disposable income decile suffer initial losses, and initial losses generally are at a manageable level. This means that there is at least one method for implementing a Citizen's Income that could be politically attractive.
Keywords: C80; H53; H55; I38; R20; 330; citizen's Income; household income; initial losses; microsimulation model